Acoustic Metamaterials - SZTYLER, Bartłomiej; STRUMIŁŁO, Paweł (Archives of Acoustics, 2022)
This review article is concerned with metamaterials, i.e. specifically engineered structures with special properties for interaction with sounds. The research on and practical design of these materials have gained momentum in the last decade, when 3D printing techniques provided the possibility to fabricate such geometrically complex structures. We briefly describe the history of research on AMMs and group them into active and passive metamaterials. For each of these groups of AMMs, we discuss the most notable construction achievements and outline the main applications. We conclude this review with a discussion of possible directions for further research and main applications of AMMs such as noise attenuation, acoustic lens, and the cloaking phenomenon.